Analisa Keruntuhan Bendungan Kering Ciawi Menggunakan Program HEC-RAS dan InaSAFE - Pramana, Fabian Raditya; Juwono, Pitojo Tri; Asmaranto, Runi (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
Dam is a structure built across a stream to retain water for the purpose of water supply, irrigation, hydropower, and flood control. Beside the high benefits, dams are also a potential threat to public safety, which is dam break/dam failure. The purpose of this study was to discover various scenarios of dam break at Ciawi Dam, with the main modes of failure have been identified as piping or overtopping. Ciawi dam break are modeled and analyzed using HEC-RAS v5.0.7 based on available geometry data. After that, based on regional population data, the economic loss calculated using InaSAFE. The simulation results showed that the Probable Maximum Flood (PMF) with a peak discharge of 1845,867 m3/s did not generate an overtopping scenario. From the analysis of 2-D simulation in HEC-RAS, the Ciawi dam break due to piping at Probable Maximum Flood (PMF) has a maximum water depth of 46,419 m with the area of inundation covers 108,04 km2. Those numbers imply that Ciawi Dam break classified as a high-hazard category.